Recommendations and guidelines for creating scholarly biomedical journals: A scoping review. - Jeremy Y Ng; Kelly D Cobey; Saad Ahmed; Valerie Chow; Sharleen G Maduranayagam; Lucas J Santoro; Lindsey Sikora; Ana Marusic; Daniel Shanahan; Randy Townsend; Alan Ehrlich; Alfonso Iorio; et al. (PLoS ONE)
Background Scholarly journals play a key role in the dissemination of research findings. However, little focus is given to the process of establishing new, credible journals and the obstacles faced in achieving this. This scoping review aimed to identify and describe existing recommendations for starting a biomedical scholarly journal. Methods We searched five bibliographic databases: OVID Medline + Medline in Process, Embase Classic + Embase, ERIC, APA PsycINFO, and Web of Science on January 14, 2022. A related grey literature search was conducted on March 19, 2022. Eligible sources were those published in English in any year, of any format, and that described guidance for starting a biomedical journal. Titles and abstracts of obtained sources were screened. We extracted descriptive characteristics including author name, year and country of publication, journal name, and source type, and any recommendations from the included sources discussing guidance for starting a biomedical journal. These recommendations were categorized and thematically grouped. Results A total of 5626 unique sources were obtained. Thirty-three sources met our inclusion criteria. Most sources were blog posts (10/33; 30.30%), and only 10 sources were supported by evidence. We extracted 51 unique recommendations from these 33 sources, which we thematically classified into nine themes which were: journal operations, editorial review processes, peer review processes, open access publishing, copyediting/typesetting, production, archiving/indexing/metrics, marketing/promotion, and funding. Conclusions There is little formal guidance regarding how to start a scholarly journal. The development of an evidence-based guideline may help uphold scholarly publishing quality, provide insight into obstacles new journals will face, and equip novice publishers with the tools to meet best practices.